Analisis Pengaruh Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Provinsi Sumatera Utara (2012-2022) - Meiriza, Mica Siar; Sembiring, Graciela Br; Sitorus, Melody; Wardana, Vidia; Sakinah, Nur (Ikatan Da'i Indonesia, 2024)
This research aims to evaluate the relationship between economic growth and poverty levels in North Sumatra during the period 2012 to 2022. The results of the research reveal that during this period, no significant relationship was found between economic growth and poverty levels in the North Sumatra region. Although economic growth is often considered a poverty reduction factor, this research indicates that other factors such as income distribution and social policies have a more dominant influence in determining poverty levels. These results highlight the importance of developing a more holistic policy strategy that includes income redistribution efforts and strengthening social protection as key measures to reduce poverty in North Sumatra. This research provides valuable insights for stakeholders in designing and implementing programs focused on poverty alleviation in the region during the period under study.